1970
DOI: 10.3329/cardio.v1i1.8218
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Infection in Intensive Care Unit - Prevention and Control

Abstract: Intensive Care Unit (ICU) is the most vulnerable area in the hospital premises. Hospital acquired infections in critically ill patients as well as of transmission of infections from a patient to another patient or to the health care workers or vice versa can occur in ICU. ICUs combine physicians, nurses and allied health professionals to manage patients with life threatening single or multiple organ system failure, including stabilization after surgical interventions. It is a continuous management including mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…DPPH, a stable free radical was scavenged by the aqueous extract of the fruit of Phoenix dactylifera in a dose dependent manner. The results were in line with that of [31] who reported that date fruits exhibited potent DPPH scavenging capacities. This suggests that scavenging of DPPH radical by hydrogen and /or electron donation by Phoenix dactylifera extract might prevent reactive radical species from reaching biomolecules such as lipoproteins, poly unsaturated fatty acids (PUFA), deoxyribonucleic acid (DNA), amino acids and proteins [32].…”
Section: 2-diphenyl-1-picrylhydrazyl (Dpph) Scavengingsupporting
confidence: 92%
“…DPPH, a stable free radical was scavenged by the aqueous extract of the fruit of Phoenix dactylifera in a dose dependent manner. The results were in line with that of [31] who reported that date fruits exhibited potent DPPH scavenging capacities. This suggests that scavenging of DPPH radical by hydrogen and /or electron donation by Phoenix dactylifera extract might prevent reactive radical species from reaching biomolecules such as lipoproteins, poly unsaturated fatty acids (PUFA), deoxyribonucleic acid (DNA), amino acids and proteins [32].…”
Section: 2-diphenyl-1-picrylhydrazyl (Dpph) Scavengingsupporting
confidence: 92%
“…Incidence of HAIs is highest in large teaching or academic hospitals. An evaluation of high-risk patients has identified many medical interventions that can also increase nosocomial infections [35]. Any type of invasive procedure can expose a patient to the possibility of infection.…”
Section: Development Of Hospital Acquired Infectionmentioning
confidence: 99%
“…[ 8 ] Neonates and pediatrics are more susceptible to get mentioned infection because of their lower degree of immunity and also unsuitable diet. [ 9 ] The most organs of which might be involved by infection are respiratory system and urinary system, and the prevalent microorganisms in these infections are Pseudomonas aeruginosa , Klebsiella pneumonia , Escherichia coli , and Candida spp. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 3 11 12 13 ] Internal factors (bacterial colonization in pharynx and stomach) and external factors (hospital's mean and staff) are ways of bacterial transmission related to VAP. [ 9 14 15 16 17 ]…”
Section: Introductionmentioning
confidence: 99%